Address to the Board of Governors, Copenhagen, September 21, 1970 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, remarked that 1970 marked the beginning of the second quarter-century of the Bank’s existence, and prefaced the opening of second development decade. He sketched out the plans for maintaining the momentum of the Bank group's accelerated activity, stressed the need for fashioning a more comprehensive strategy for development, and welcomed the publication of the Pearson Commission report.